Classical Music Contemporary Perspectives and Challenges - Beckerman, Michael; Boghossian, Paul (Open Book Publishers, 2021)
"This kaleidoscopic collection reflects on the multifaceted world of classical music as it advances through the twenty-first century. With insights drawn from leading composers, performers, academics, journalists, and arts administrators, special focus is placed on classical music's defining traditions, challenges and contemporary scope. Innovative in structure and approach, the volume comprises two parts. The first provides detailed analyses of issues central to classical music in the present day, including diversity, governance, the identity and perception of classical music, and the challenges facing the achievement of financial stability in non-profit arts organizations. The second part offers case studies, from Miami to Seoul, of the innovative ways in which some arts organizations have responded to the challenges analyzed in the first part. Introductory material, as well as several of the essays, provide some preliminary thoughts about the impact of the crisis year 2020 on the world of classical music. Classical Music: Contemporary Perspectives and Challenges will be a valuable and engaging resource for all readers interested in the development of the arts and classical music, especially academics, arts administrators and organizers, and classical music practitioners and audiences."